(untitled) (Social Science Review, 2021)
The core objective of the study is to explore empirically the determinants of the capital structure measured in terms of leverage and the existence of linkages in the capital structure of the companies enlisted in the Dhaka Stock Exchange (DSE) using the recent ten years’ historical annual data from 2006 to 2015. The theoretical attributes of the capital structure have been examined using the tangibles assets, profitability, size of the company, and growth opportunity as explanatory variables. Findings from the Feasible Generalized Least Square (FGLS) reveal that tangibility, size, and growth opportunity contributes positively to the capital structure whereas profitability impacts the capital structure negatively. These findings might have serious policy implications for achieving desired capital structure for the companies enlisted in the DSE. Social Science Review, Vol. 37(2), Dec 2020 Page 27-41